Coupling Relationship of Leaf Economic and Hydraulic Traits of Alhagi sparsifolia Shap. in a Hyper-Arid Desert Ecosystem - Yin, Hui (2021)
In this study, Alhagisparsifolia Shap. was used to test the hypothesis that leaf economic and hydraulic traits are coupled in plants in a hyper-arid region. Five economic traits and six hydraulic traits were examined to explore the relationship. Results showed that the stomatal density (SD) on both surfaces was coupled with maximum stomatal conductance to water vapor (gwmax) and leaf tissue density (TD). SD on adaxial surface (SDaba) was significantly positively related to vein density (VD) but negatively related to leaf thickness (LT) and stomatal length on adaxial surface (SLada). Nitrogen concentration based on mass (Nmass) was significantly negatively correlated with leaf mass per area (LMA), LT, and VD, whereas nitrogen concentration based on area (Narea) was significantly positively related to LMA and TD. Mean annual precipitation (MAP) contributed the most to the changes in LT and stomatal length (SL). Soil salt contributed the most to TD, SD, and gwmax. Soli nutrients influenced the most of LMA and VD. Mean annual temperature contributed the most to Nmass and Narea. In conclusion, the economics of leaves coupled with their hydraulic traits provides an economical and efficient strategy to adapt to the harsh environment in hyper-arid regions.